2016
DOI: 10.1021/acs.jpcc.6b02131
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Novel Derivatives with Giant Second Hyperpolarizabilities, Based on Radiaannulenes, Tetrathiafulvalene, Nickel Dithiolene, and Their Lithiated Analogues

Abstract: The main goal of this study was the design/ recognition of a series of derivatives with exceptionally large hyperpolarizabilities, the understanding of the mechanism through which these properties are derived, and the generalization of the resulting findings. Thus, we have studied the structure, a series of properties involving the excitation energies and the diradical character, but mainly the (hyper)polarizabilities of some oligomers of radiaannulene-tetrathiafulvalene (RA-TTF), radiaannulene-bis(ethylene-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 102 publications
1
22
0
Order By: Relevance
“…For this purpose, it has been well-established in the literature that the computational theoryaided design can be a useful tool to optimize the molecular electro-optic performance. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Recently, several works [45][46][47][48][49][50][51][52][53][54][55] have evaluated the NLOP of Hückel and Möbius topologies. For instance, the present authors studied the electronic and vibrational contributions to static and dynamic NLOP of the Hückel-Möbius switch of the bianthraquinodimethane modified [16] annulene 56,57 and A,D-di-p-benzi [28]hexaphyrin(1.1.1.1.1.1).…”
Section: ) Introductionmentioning
confidence: 99%
“…For this purpose, it has been well-established in the literature that the computational theoryaided design can be a useful tool to optimize the molecular electro-optic performance. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Recently, several works [45][46][47][48][49][50][51][52][53][54][55] have evaluated the NLOP of Hückel and Möbius topologies. For instance, the present authors studied the electronic and vibrational contributions to static and dynamic NLOP of the Hückel-Möbius switch of the bianthraquinodimethane modified [16] annulene 56,57 and A,D-di-p-benzi [28]hexaphyrin(1.1.1.1.1.1).…”
Section: ) Introductionmentioning
confidence: 99%
“…Most of the presented here results have been computed by using the (U)­CAM-B3LYP functional with the 6-31G* basis set for H, C, Ο, F, and S, atoms. , The quasi-relativistic, effective core potential ECP28MWB­(SDD) has been employed for Ni . A detailed study on the performance of CAM-B3LYP/6-31G*, for NiBDT derivatives, has been reported . The satisfactory performance of the procedure we employ has been confirmed by comparing the DFT results with the more rigorous CASSCF/CASPT2 [complete active space multiconfiguration SCF/CAS second order perturbation theory] and CCSD­(T) [coupled-cluster with single, double and perturbative triple excitations (CCSD­(T))] ones .…”
Section: Methodsmentioning
confidence: 85%
“…25 A recent theoretical study has also shown that such compounds are interesting for their nonlinear optical properties. 26 The first synthesis 23b (Scheme 11) did not involve gold(I) alkynyl complexes. Instead, the trimethylsilyl groups of TEE 22 were removed selectively using K 2 CO 3 in MeOH and THF,…”
Section: Figure 4 Tee Derivatives With Terminal Gold(i) Complexesmentioning
confidence: 99%